2018
DOI: 10.5863/1551-6776-23.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Clinical Outcomes With Cefepime in a Neonatal Intensive Care Unit: A Retrospective Cohort Study

Abstract: OBJECTIVES The objective of this study was to characterize clinical outcomes when cefepime was used in a neonatal intensive care population. METHODS Data were extracted from the medical records of all full-term (40 weeks gestational age) patients up to 2 months of age and preterm patients up to 48 weeks postmenstrual age admitted to the neonatal intensive care unit (NICU) at a freestanding children's hospital between January 1, 2010, and December 31, 2013, who received at least 48 hours of cefep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
(36 reference statements)
2
6
0
Order By: Relevance
“…This study showed that cefepime was frequently indicated for complicated urinary tract infections, post‐dialysis complications, and sepsis. These findings are in line with previous studies 15,16,38 …”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…This study showed that cefepime was frequently indicated for complicated urinary tract infections, post‐dialysis complications, and sepsis. These findings are in line with previous studies 15,16,38 …”
Section: Discussionsupporting
confidence: 94%
“…As in a previous study, clinical improvement was significantly associated with appropriate dose, indication, and antibiogram results 16 . In this study, positive clinical outcome was observed in fifty percent of patients despite the inadequate antibiograms and very low adherence to dose and duration of cefepime therapy.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations